Pengembangan Media Pembelajaran Kosakata Bahasa Arab berbasis Barcode Interaktif di Kelas VI MI Nurul Falah Muaro Jambi - Nuraini, Widya; Al Ghozali, M. Dzikrul Hakim (YASIN, 2025)
Arabic vocabulary learning at the madrasah ibtidaiyah level continues to face several challenges, including students' low memory retention, the use of monotonous teaching methods, and limited access to interactive learning media. At MI Nurul Falah Muaro Jambi, these issues are evident among sixth-grade students who struggle to understand and retain vocabulary. This study aims to develop an interactive barcode-based Arabic vocabulary learning medium, assess its validity, and evaluate its effectiveness in improving students’ vocabulary mastery. The research employed a Research and Development (R&D) method using the ADDIE model, which encompasses the stages of Analysis, Design, Development, Implementation, and Evaluation. Data were collected through expert validation, classroom observation, learning outcome tests (pre-test and post-test), and teacher and student response questionnaires. The results indicate that the developed learning medium achieved an average validity score of 88.4%, categorized as “highly valid and feasible.” Effectiveness testing revealed a significant improvement in student learning outcomes, with average scores rising from 51.1 on the pre-test to 86.4 on the post-test. These findings suggest that the interactive barcode-based learning medium is not only valid but also effective in enhancing Arabic vocabulary acquisition at the madrasah ibtidaiyah level. The implication is that simple technologies such as barcodes can serve as innovative solutions that support improved learning outcomes, student motivation, and learner autonomy, while aligning with the implementation of the Kurikulum Merdeka.